PENGARUH PENGALAMAN KERJA, STRES KERJA, KOMPENSASI FINANSIAL, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEMERIKSA PAJAK (Studi Empiris pada Pemeriksa Pajak di KPP Madya Pekanbaru dan KPP Madya Batam) - Elisa Natalia Siahaan; Zirman -; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect caused by the variable work experience, job stress, financial compensation, and work environment on the performance of tax inspectors in KPP Madya Pekanbaru and KPP Madya Batam. This study uses a sampling technique saturated with 64 samples. Data collection techniques in this study is in the form of a questionnaire, while the data analysis technique used is multiple regression analysis were processed with SPSS version 17 for windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the performance variable tax inspectors. Partial regression test (t test) showed that the variables work stress, financial compensation, and working environment partially affect the variables performance of tax inspectors, while the partial work experience variables do not affect the variables performance of tax inspectors. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 63.0%, while the remaining 37.0% is influenced by other variables not examined in this study.Keywords: work experience, job stress, financial compensation, work environment, and the performance of tax inspectors